Penerapan Model Pembelajaran Kooperatif Tipe Make a Match Untuk Meningkatkan Sikap Kerja Sama dan Hasil Belajar Siwa pada Pembelajaran Tematik di Kelas IV SDN 45 Kota Bengkulu - teta herlina; Sri Dadi; Panut Setiono (JURIDIKDAS, 2022)
This study aims to improve the attitude of cooperation and learning outcomes of the class IVA students at Elementary School 45 Bengkulu City by applying cooperative learning model with Make a Match type. This research is a Classroom Action Research. The subjects in the study amound to 19 students with 9 female and 10 male students. The research instruments used are observation and test sheets. The data analysis techniques in this research observation sheet that uses the formula for the average score, the highest score, the lowest score, the difference in score and the range of values for each criterion. The test data was analyzed using the formula of average values and the classical learning percentage. The average results of implementation cooperative learning model type Make a Match of first cycle is 62.50 enough categories. The increase second cycle which is 89.50 very good categories. The average cooperation attitude result of the first cycle is 7.38 in the enough categories. The increase second cycle which is 13.53 very good categories. The results of learning ips subjects, first cycle average was 69.74 with classical completion of 63.16%. The second cycle is percentage more increase then the first cycle that is 81.84 with classical completion of 89.47%. The result of learning Bahasa Indonesia subject, first cyle average was 70.92 with classical completion of 57.89%. The second cycle is percentage more increase then the first cyle that is 83.82 with classical completion of 89.47%. There fore, the implementation of the Make a Match type of cooperative learning model can increase cooperation attitudes and learning outcomes of students in thematic learning in class IVA Elementary School 45 Bengkulu City,